CO2 methanation over nickel-CeO2 catalyst supported on Al2O3: Different impregnation strategies and Ni-Ce ratios - de Piano, Gabriel; Andrade Gamboa, Julio José; Condo, Adriana Maria; Gennari, Fabiana Cristina (Pergamon-Elsevier Science Ltd, 2024)
Fil: de Piano, Gabriel. Universidad Nacional de Cuyo; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina